Impact of COVID-19 and intensive care unit capacity on vaccination support: Evidence from a two-leg representative survey in the United Kingdom - Géraldine Blanchard-Rohner; Bruno Caprettini; Dominic Rohner; Hans-Joachim Voth (Elsevier, 2021)
Background: Overcoming coronavirus disease (COVID-19) will likely require mass vaccination. With vaccination scepticism rising in many countries, assessing the willingness to vaccinate against COVID-19 is of crucial global health importance. Objective: The goal of this study was to examine how personal and family COVID-19 risk and ICU (intensive care unit) availability just before the pandemics influence the acceptance of future COVID-19 vaccines. Methods: A two-leg survey was carried out for comparing vaccination attitudes pre-and post-COVID-19. UK residents were surveyed in October 2019 about their vaccination attitudes, and again in a follow-up survey in April 2020, containing the previous questions and further ones related to COVID-19 exposure and COVID-19 vaccine attitudes. The study combined survey results with local COVID-19 incidence and pre-COVID-19 measures of ICU capacity and occupancy. Regression analysis of the impact of individual and public health factors on attitudes towards COVID-19 vaccination was performed. Results: The October 2019 survey included a nationally representative sample of 1653 UK residents. All of them were invited for the follow-up survey in April 2020, and 1194 (72%) participated. The April 2020 sample remained nationally representative. Overall, 85% of respondents (and 55% of vaccine sceptics) would be willing to be vaccinated against COVID-19. Higher personal and family risk for COVID-19 was associated with stronger COVID-19 vaccination willingness, whereas low pre-COVID-19 ICU availability was associated with lower trust in medical experts and lower COVID-19 vaccine support. Further, general vaccination support has risen during the COVID-19 pandemic. Conclusion: Support for COVID-19 vaccination is high amongst all groups, even vaccine sceptics, boding well for future vaccination take-up rates. Vaccination willingness is correlated with health care availability during the COVID-19 crisis, suggesting a powerful synergy between health care system performance during crisis and the general population's trust in the medical profession - as reflected in vaccination support.